UTILIZATION OF DIGITAL SHORT STORIES IN TEACHING VOCABULARY (Web of Teachers: Inderscience Research, 2024)
Since educators now have easier access to digital tools such as scanners, digital cameras, PCs, and user-friendly software, the adoption of new technologies in education has grown globally in recent years. The majority of the effects of new technology in educational settings have been favorable since they have helped teachers improve their knowledge and abilities, which has raised educational standards. Researchers have discovered that integrating these technologies improves student motivation, achievement, and engagement. Education systems still have a lot of work ahead of them, one of which is figuring out how to increase student involvement to improve academic results. The utilization of creative instructional strategies to engage students has grown in significance. One of the creative and useful strategies that might get students interested in in-depth, meaningful learning is the use of digital short stories. The purpose of this research effort was to use digital short stories to increase learners' vocabulary. The study looked into the advantages of using digital short stories as well as how they affect student's learning when they are used by both teachers and students.